Corporate Social and Environmental Responsibility in an Emerging Economy: Through the Lens of Legitimacy Theory - Asit Bhattacharyya (Australasian Accounting, Business and Finance Journal, 2015)
Efforts to promote Corporate Social and Environmental Responsibility (CSER) require an understanding of stakeholder attitudes toward enhanced responsibility. However, little is known about current attitudes on this subject, or the determinants of these attitudes. This study presents a survey of the attitudes of Indian managers, toward 18 social and 16 key contemporary environmental management issues. The findings indicate that respondents are concerned about a range of issues surrounding social responsibility. With respect to environmental responsibilities, Indian respondents were also strong in their support, and identified a select few issues to be more important over other environmental factors. Results indicated a positive attitude of Indian managers towards CSER. Confirmatory factor analysis (CFA) confirmed three distinct social and environmental factors for the respondents and provided a model of managerial attitudes towards CSER.
Keywords: CSER; social responsibility; Emerging economy; Legitimacy theory; India